PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGGULANGI BULLYING DI SDN 1 KALAMPANGAN - Ery Nofrizal; Santiani; Yatin Mulyono; Asmawati (CV. Adiba Aisha Amira, 2026)
This study aims to identify the role of Islamic Education (PAI) teachers in addressing bullying behavior at SDN 1 Kalampangan. The research employed a qualitative descriptive approach with students and the Islamic Education teacher as the main subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Islamic Education teachers play a strategic role in preventing and handling bullying through three main functions: as educators, role models, and spiritual mentors. They instill moral and ethical values (akhlakul karimah), guide students to understand Islamic teachings regarding compassion and the prohibition of harming others, and foster a religious and harmonious school atmosphere. Efforts include integrating Islamic values into the learning process, promoting mutual respect among students, and collaborating with schools and parents. The main obstacles encountered are low student awareness of bullying’s impact and limited supervision outside class hours. The study concludes that collaboration among teachers, schools, and families is essential to create a safe, religiously grounded, and bullying-free educational environment